Building a Government Based on the Rule of Law History and Development - Ma, Huaide (Research Series on the Chinese Dream and China's Development Path,, 2018)
This book offers a comprehensive assessment of the successes and failures in China's current legal system construction. It systematically and comprehensively examines the development of China's rule of law policy since the reform and opening up, as well as future trends. The main areas covered include: The course, achievements and motivation behind China's construction of law-based administration; Development, status quo and general characteristics of administrative legislation; Reform of the administrative examination and approval system and the administrative licensing system; The relationship between social security system reform, beneficial administration and service government; The development of administrative law in China; Origin of the concept of due process, experiences with and development trends concerning China's administrative legislative procedure; The importance of government information, open practices, problems and development trend; History, current situation, reform mechanism of the emergency management system and the improvement of the legal system for emergency requisitions; The course, practical problems in and reasons for the enhanced approach of administrative reconsideration system; The course, achievements in, current situation and enhanced approach of administrative litigation system; The course of the national compensation system; and the construction of responsible government and administrative accountability system.